Effects of Using the WhatsApp Application on Iranian Intermediate EFL Learners’ Vocabulary Learning and Autonomy - Janfeshan, Kamran; Nader Sharhan, Asmaa; Janfeshan, Mohamad Mahdi (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2023)
The current study was designed to determine if the use of blended learning (combining face-to-face instruction and mobile-assisted language learning using WhatsApp) contributed to the vocabulary learning and autonomy of Iranian English as a foreign language (EFL) learners, compared to the traditional method. To assess their English skills, the Preliminary English Test (PET) was given to 80 homogenous intermediate learners at the beginning of the study. The study’s intended participants were 50 EFL learners whose scores were within the intermediate competency level. Then, the participants were divided randomly betweenexperimental and control groups. One-way between-groups analysis of covariance was run. Findings frompost-test scores indicated a statistically significant difference between the experimental and control groups. Another one-way between-groups analysis of covariance was performed to assess the impact of two distinct blended learning versus traditional teaching treatments on EFL learners’ autonomy. In the post-test results, a significant difference between the control and experimental groups’ performance was observed. This study provided insights into how technology may be applied to teach language components and skills.